Reduced cortical thickness in body dysmorphic disorder. (30th January 2017) - Grace, Sally A.; Buchanan, Ben G.; Maller, Jerome J.; Toh, Wei Lin; Castle, David J.; Rossell, Susan L.
Abstract: Recent neuroimaging studies in body dysmorphic disorder (BDD) have implicated abnormal structure and function of occipito-temporal and fronto-limbic regions in the potential pathophysiology of the disorder. To date, morphometric investigations have yielded inconsistent results, and have suggested that clinical symptoms may mediate structural brain abnormalities in BDD. We measured Grey Matter (GM) cortical thickness in 20 participants with BDD and 20 healthy control participants matched on age, gender, estimated IQ and handedness. We observed cortical thinning in BDD patients compared with healthy control participants within the left middle temporal and left inferior parietal gyrus. No significant relationships between cortical thickness and BDD symptom severity, insight, social anxiety and depression were observed within the BDD group. Thinning within left temporal and left inferior parietal regions supports the involvement of these regions in the pathophysiology of BDD.